Structural, Thermal and Film forming properties of Gelatin from Pink Perch Surimi Refiner Discharge - Hanjabam, M. D.; Balange, A. K.; Zynudheen, A. A. (Fishery Technology, 2017)
The objective of the present study was to characterize the gelatin obtained from pink perch (Nemipterus japonicus) surimi refiner discharge [referred as refiner discharge gelatin (RDG)] with reference to its structural, thermal and film forming ability. Fourier transform infrared (FTIR) and Differential Scanning Calorimetry (DSC) techniques were used to characterize the gelatin. An edible film was developed with different concentrations of RDG (2-6%) by casting method. FTIR analysis showed that the gelatin from refiner discharge has similar spectra with porcine gelatin (PG). The amide I and amide II bands of RDG occurred at around 1654 and 1578 cm-1 respectively. RDG has a broad endothermic peak at 85.64oC with transition enthalpy (Î”H) of 208.02 J g-1 as revealed by thermal analysis indicating the thermal transition temperature and the energy required for the transition respectively. RDG showed good film forming property. The gelatin concentration had strong significant (p<0.05) effect on the viscosity of film forming solution. Films were more opaque at higher concentration of gelatin compared to the films prepared at lower concentration. Higher L* values were observed for all the films prepared and there were no significant differences among the gelatin concentrations. Tensile strength of the film increased with increasing gelatin concentration whereas the film swelling was found to be decreased. The study clearly demonstrated that the waste from the surimi processing industries like refiner discharge can be an alternative raw material for gelatin production and can be used for edible packaging films development.